Vincristine, Irinotecan, and Bevacizumab in Relapsed Wilms Tumor With Diffuse Anaplasia. Issue 4 (May 2018) - Schiavetti, Amalia; Varrasso, Giulia; Collini, Paola; Clerico, Anna
Abstract : The prognosis of relapsed Wilms tumor (WT) with diffuse anaplasia is dismal, therefore, novel therapeutic strategies need to be explored. We reported on 2 consecutive cases with relapsed anaplastic WT who presented a partial response after 2 courses of vincristine, irinotecan, and bevacizumab association. This regimen may have a role in the treatment of patients with anaplastic advanced WT.